Development of E-Module Teaching Materials Based on Socio-Scientific Issues to Improve Students’ Science Literacy on The Global Warming Topic - Amalia Cahya Anggraheni; Ulfa Lutfianasari (Universitas Negeri Semarang, 2025)
Indonesian education has undergone a curriculum change in the form of the